Русский щит: роман-хроника / Вадим Каргалов - Каргалов Вадим Викторович (Витязь, 1994)
Экземпляры: аб. (1995) / Инвентарный номер: 38065 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 21 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-442